Effects of Beak Trimming on Pecking Force - Dennis, Rachel L.; Cheng , Heng W. (International Journal of Poultry Science, 2010)
Beak trimming of the production laying hen has come under great scrutiny by welfare and consumer advocacy groups as a potential source of acute and chronic pain as well as having the potential to inhibit the freedom to express normal behaviors such as feeding behaviors. Although several studies have shown evidence of immediate pain response from beak trimming, the long term effects on bird welfare are not well understood. In the present study we investigated the force with which chicks peck during feeding. Chicks were beak trimmed using hot blade trimming at 2 days of age and were tested on a force plate at 3, 4 and 5 weeks of age. Both the time spent pecking and the forces of those pecks were measured. Beak trimmed birds spent significantly less time pecking at the feed and used less force than untrimmed birds at 3 weeks of age (p<0.05). However, at 4 and 5 weeks of age the difference was no longer significant (p>0.05). Beak trimmed birds also had a higher pecking ratio (peck force:time, p<0.05) than untrimmed birds. The difference was no longer apparent at 4 and 5 weeks of age (p>0.05). Our data suggest that beak trimming alters feeding behavior at a young age. However, changes in pecking force and time spent feeding were not long lasting and became similar to those of untrimmed birds after 3 weeks post-trimming.